OTOMATISASI PENGUJIAN PERFORMA APLIKASI E-COMMERCE GUNA MENINGKATKAN KEANDALAN DENGAN JMETER: OTOMATISASI PENGUJIAN PERFORMA APLIKASI E-COMMERCE GUNA MENINGKATKAN KEANDALAN DENGAN JMETER - Prayoga, Yudi; Ananda Vadhiel Mali; Muhammad Rangga Prasetya; Ade Dwi Irawan (Journal of Research and Publication Innovation, 2024)
Automating application performance testing is a crucial strategy in modern software development. One of the commonly used tools for this purpose is Apache JMeter. JMeter enables developers to create realistic test scenarios to measure the performance of an application under various workload conditions. By automating with JMeter, developers can identify and address potential performance issues before the application is introduced to end users, thereby enhancing the reliability and overall quality of the application. In this abstract, we will explore the basic concepts of automated performance testing with JMeter and how its use can improve application reliability.